2014
DOI: 10.1111/jgs.13061
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the 2008 U.S. Preventative Services Task Force Recommendation on Frequency of Prostate‐Specific Antigen Screening in Older Men

Abstract: The 2008 recommendation appeared to reduce PSA screening rates in older men in 2009 and 2010; there was a substantial reduction in men aged 75 and older and a more modest reduction in men aged 65 to 74.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 25 publications
(35 reference statements)
1
7
1
Order By: Relevance
“…However, our findings regarding the unclear impact of guidelines on screening rates contradict several previous reports that attribute changes in cancer screening trends to published guidelines, [46][47][48][49] although the literature is mixed [50][51][52] and the results are difficult to compare due to different study populations, procedure inclusion criteria, and data sources (billing or survey data). Several of these other studies used more granular data to examine screening rates before and after the publication of a specific guideline, which allows for more precise quantification of the guideline's impact than the descriptive analysis across multiple sites emphasized in our report.…”
Section: Discussioncontrasting
confidence: 98%
“…However, our findings regarding the unclear impact of guidelines on screening rates contradict several previous reports that attribute changes in cancer screening trends to published guidelines, [46][47][48][49] although the literature is mixed [50][51][52] and the results are difficult to compare due to different study populations, procedure inclusion criteria, and data sources (billing or survey data). Several of these other studies used more granular data to examine screening rates before and after the publication of a specific guideline, which allows for more precise quantification of the guideline's impact than the descriptive analysis across multiple sites emphasized in our report.…”
Section: Discussioncontrasting
confidence: 98%
“…Two recent reviews indicated that screening rates have declined, but these reviews synthesized heterogeneous data including self‐reports (which have been shown to be biased), small areas, and different time periods. Two studies that used objective screening measures spanning 2008 to 2012 showed the same pattern as ours, whereas others using shorter time periods or limited areas showed only declining rates . We found no prior studies of change in PSA screening rates in response to guidelines according to race, although two studies found no differential effect of race when examining referral or stage of disease .…”
Section: Discussionsupporting
confidence: 72%
“…Two studies that used objective screening measures spanning 2008 to 2012 showed the same pattern as ours, 43,44 whereas others using shorter time periods or limited areas showed only declining rates. [45][46][47][48][49][50] We found no prior studies of change in PSA screening rates in response to guidelines according to race, although two studies found no differential effect of race when examining referral or stage of disease. 51,52 Our study has the advantage over these prior studies of using consistent measures of PSA testing well before and after evidence change, with a large enough sample to examine heterogeneity of change across subgroups of men and across areas.…”
Section: Discussionmentioning
confidence: 71%
“…The differing recommendations for prostate cancer screening have created confusion for primary care providers (PCPs). Previous studies reported that these guidelines reduced PSA screening rates in men >75 years , although studies of self‐reported PSA testing and PCP PSA ordering have not .…”
Section: Introductionmentioning
confidence: 99%